2007
DOI: 10.1107/s1600536807001444
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Diaminopyridine

Abstract: Key indicatorsSingle-crystal X-ray study T = 120 K Mean (C-C) = 0.003 Å R factor = 0.036 wR factor = 0.081 Data-to-parameter ratio = 8.4For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 3 publications
2
21
0
Order By: Relevance
“…In the case of the hydrogensquarate salt of 34-DAP [15], interactions of the types NHÁÁÁO=C (Sq) with a bond length of 2.800 Å and NH 2 ÁÁÁO=C (Sq) with bond lengths of 2.969 and 2.974 Å are observed, while in 3,4-diaminopyridinium hydrogentartarate dihydrate [16] a 3D network with molecules linked by intermolecular NHÁÁÁOH 2 (2.807 Å ), HNHÁÁÁOH 2 (3.037 Å ), HNHÁÁÁOCO (3.007 Å ), HOHÁOCO (2.680 Å ), OHÁÁÁOH 2 (2.789 Å ), and HOHÁÁÁOH (2.747 Å ) hydrogen bonds with participation of cations, anions, and solvent molecules is obtained. It is in contrast to neutral 3,4-DAP [14], where both the 3-and 4-NH 2 substituents participate in symmetric intermolecular hydrogen bonding of the type HNHÁÁÁN with bond lengths of 2.258, 2.228 Å (for 4-NH 2 ) and 2.327 and 2.496 Å (for 3-NH 2 ). The molecule of the cation is flat with a maximal deviation from total planarity less than 0.2°.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In the case of the hydrogensquarate salt of 34-DAP [15], interactions of the types NHÁÁÁO=C (Sq) with a bond length of 2.800 Å and NH 2 ÁÁÁO=C (Sq) with bond lengths of 2.969 and 2.974 Å are observed, while in 3,4-diaminopyridinium hydrogentartarate dihydrate [16] a 3D network with molecules linked by intermolecular NHÁÁÁOH 2 (2.807 Å ), HNHÁÁÁOH 2 (3.037 Å ), HNHÁÁÁOCO (3.007 Å ), HOHÁOCO (2.680 Å ), OHÁÁÁOH 2 (2.789 Å ), and HOHÁÁÁOH (2.747 Å ) hydrogen bonds with participation of cations, anions, and solvent molecules is obtained. It is in contrast to neutral 3,4-DAP [14], where both the 3-and 4-NH 2 substituents participate in symmetric intermolecular hydrogen bonding of the type HNHÁÁÁN with bond lengths of 2.258, 2.228 Å (for 4-NH 2 ) and 2.327 and 2.496 Å (for 3-NH 2 ). The molecule of the cation is flat with a maximal deviation from total planarity less than 0.2°.…”
Section: Resultsmentioning
confidence: 91%
“…3 is compared with the corresponding one of neutral molecule and its N1 protonated form [14][15][16]. In contrast to N1 monoprotonated salts [15,16], the N1, N4 diprotonation leads in the calculated IR-spectrum to an observation of the highest frequency bands, corresponding to asymmetric and symmetric stretches (m as NH 2 and m s NH 2 ) of 3-NH 2 group at 3,560 and 3,461 cm -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The computed bond parameters of the preferred optimized geometry of the chosen molecules at DFT level with 6-311G+ + (d, p) basis set are summarized in the Table-1in addition to the experimental parameters [18] for comparative purpose. Values taken from Ref.…”
Section: Analysis Of Geometric Parametersmentioning
confidence: 99%
“…Values taken from Ref. [18] Molecular symmetry is a fundamental concept as it is a tool to predict the properties such as dipole moment, planar structure of aromatic ring and electronic transitions in the molecules. It is observed that the mean C-C bond distance estimated in between the carbon atoms of the pyridine ring are found to be 1.395Å, 1.397 Å, 1.396 Å and 1.388 Å for 2AP, 3AP, 4AP and 34DAP respectively and these values are not significantly deviated from one another although they contain -NH 2 group at different positions.…”
Section: Analysis Of Geometric Parametersmentioning
confidence: 99%